Demographic differences in accumulated types of capital in Massively Multiplayer Online Role-Playing Games - Henry Korkeila; Jonna Koivisto; Juho Hamari (United States, 2022)
This paper examines how the demographic attributes and extra-game habits of players of a Massively Multiplayer Online Role-Playing Game (MMORPG) predict the accumulated capital of their avatars. An online survey (N=905) was conducted amidst the players of Final Fantasy XIV (FFXIV). Four types of capital were measured to map out the concrete and intangible resources of the avatars; social, economic, cultural and symbolic. The results show that weekly time spent playing the game is the strongest predictor of avatar capital and was associated with all types of capital. Time subscribed to the game was associated with cultural, economic, symbolic and bonding social capital. Social capital was found to be highest amongst both young and female players. Forum activity was associated with symbolic capital.
AcademicMindtrek '20: Proceedings of the 23rd International Academic Mindtrek Conference